A construção da liberdade religiosa em Portugal: do trilho legal à percepção da liberdade religiosa entre as lideranças evangélicas = Building religious freedom in Portugal: from the legal trail to the perception of religious freedom among evangelical leaders - Moniz, Jorge Botelho (Rever, 2020)
Today, 90% of the countries in the world already have clauses on religious freedom in their key legal texts. In view of this, one might ask: what is yet to be discussed regarding this subject? Have we not achieved an end of history concerning religious freedom? In fact, the Portuguese case, while usually claimed as a good example of religious freedom, continues to challenge this assumption. Our work focuses precisely on the analysis of these challenges. Through a questionnaire applied to evangelical leaders in Portugal, we analyze the perception of religious freedom in the country. We conclude that, although there is a well-defined system of State-religious separation and a relatively advanced regime of religious freedom, in Portugal there seems to be a certain dichotomy between de facto and de jure religious freedom.